Blood-pressure measurement - Bimo Sunarfri Hantono (2008)
In this project an auscultatory method is used to obtain non-invasive human blood-pressure signals. An algorithm based on wavelet transform is introduced to detect every single Korotkoff pulse of blood pressure for (1) a subject at rest, (2) a subject walking with his/her arm still and (3) a subject walking with his/her arms swinging.